Installing the seal exhibit - Field Museum of Natural History (1947)
Emil Sella works on the snow inside the Weddell's Seal diorama. The specimens were originally collected on the 2nd Antarctic Expedition of 1934-1935 under the leadership of Rear-Admiral Richard E. Byrd.